Carbon Leaching from Tropical Peat Soils and Consequences for Carbon Balances - Rixen, Tim; Baum, Antje; Wit, Francisca; Samiaji, Joko (Frontiers in Earth Science, 2016)
Drainage and deforestation turned Southeast (SE) Asian peat soils into a globally important CO2 source, because both processes accelerate peat decomposition. Carbon losses through soil leaching have so far not been quantified and the underlying processes have hardly been studied. In this study, we use results derived from nine expeditions to six Sumatran rivers and a mixing model to determine leaching processes in tropical peat soils, which are heavily disturbed by drainage and deforestation. Here we show that a reduced evapotranspiration and the resulting increased freshwater discharge in addition to the supply of labile leaf litter produced by re-growing secondary forests increase leaching of carbon by ~200%. Enhanced freshwater fluxes and leaching of labile leaf litter from secondary vegetation appear to contribute 38% and 62% to the total increase, respectively. Decomposition of leached labile DOC can lead to hypoxic conditions in rivers draining disturbed peatlands. Leaching of the more refractory DOC from peat is an irrecoverable loss of soil that threatens the stability of peat-fringed coasts in SE Asia.